Gibberellin Response in Lettuce Hypocotyl Sections - Silk, Wendy Kuhn (1975)
Excised lettuce (Lactuca sativa L.) hypocotyl sections retain the ability to elongate in response to gibberellic acid (GA(3)) addition. In 48 hr at 30 C a GA(3)-treated segment more than doubles while a control segment elongates less than 50%. Auxin has no detectable effect on this system. Sensitivity to GA(3) is not decreased by apex or root removal. Of the experimental variables tested, temperature, sucrose, and preincubation in water affect growth both with and without GA(3). Blue and far red light inhibit growth without GA(3); this inhibition is reversed by GA(3). Potassium chloride stimulates growth of illuminated sections treated with GA(3) but has no effect on control growth. When sections are incubated in the dark, KCl has a promotive effect on elongation.